Performance evaluation for various monitors used in a clinical environment for medical image analysis (Research, Society and Development, 2023)
This article aims to evaluate the performance of dedicated and common monitors used for medical reporting. Eleven monitors employed for medical reporting in a public hospital were assessed, including one 2 MP monitor, two 5 MP monitors, and eight common-use monitors employed for medical image evaluation. The tests analyzed monitor luminance, room illuminance specific to each equipment's use, luminance uniformity, noise, resolution, and the luminance response curve as indicated by the publication of AAPM Report 270. Regardless of their purpose, dedicated or common use, the monitors displayed significant deviations in the luminance measurements, which impacted their luminance response curve. However, the assessment of luminance uniformity complied with the limits established by legislation. Similarly, illuminance and resolution met the requirements set by regulations. Only two of the dedicated-use monitors, namely Barco left and right, conformed to the limits established for primary monitors regarding noise and maximum luminance measurements. In contrast, the common-use monitors did not meet the minimum noise evaluation criteria to be considered primary monitors, but with respect to maximum luminance, only two of the devices failed to reach the minimum values. The evaluated monitors do not meet the standards set by ANVISA and AAPM, indicating the need for recalibration of dedicated use equipment and the incompatibility of common-use devices for medical reporting.